2013
DOI: 10.1016/j.snb.2012.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle biosensor: A method for direct label-free real time protein detection

Abstract: Here we present the development of an array of electrical micro-biosensors in a microfluidic channel, called microneedle biosensors. A microneedle biosensor is a real-time, label-free, direct electrical detection platform, which is capable of high sensitivity detection, measuring the change in ionic current and impedance modulation, due to the presence or reaction of biomolecules such as proteins and nucleic acids. In this study, we successfully fabricated and electrically characterized the sensors and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…We patterned the nanoneedle bundles by etching the 200 nm top-SiO 2 layer; 100 nm top pþ-silicon layer, and 30 nm middle oxide layer,100nmpþ-silicon layer down to bottom oxide layer. [53][54][55][56][57] We performed wet etch step to etch out the channel below the bundle of nanoneedles. Afterwards, we performed another etch step to expose the bonding pads to allow wire bonding.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…We patterned the nanoneedle bundles by etching the 200 nm top-SiO 2 layer; 100 nm top pþ-silicon layer, and 30 nm middle oxide layer,100nmpþ-silicon layer down to bottom oxide layer. [53][54][55][56][57] We performed wet etch step to etch out the channel below the bundle of nanoneedles. Afterwards, we performed another etch step to expose the bonding pads to allow wire bonding.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…Various miniaturization techniques have been introduced for detection of proteins [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], nucleic acids [10,16,21], and cells [22][23][24][25][26][27]. These techniques are unsuitable for metabolites because tagging the metabolite with beads or a fluorophore would alter the structure significantly and affect the binding of the target metabolite to the probe antibody.…”
Section: Metabolite Detectionmentioning
confidence: 99%
“…Several electrochemical genosensors have been reported that have nanomolar-range sensitivity, but all to date rely on labeling techniques (Kannan 2011; Hashemi Rafsanjani et al 2010). Labeling is an expensive, time-consuming, and labor-intensive procedure that introduces additional uncertain sources of error to the measurements (Esfandyarpour et al 2013; Kricka 2002). Silicon Nanowires (SiNWs), one of the more sensitive and selective technologies for the detection of DNA hybridization, is quite limited in throughput (Park et al 2002; Li et al 2004; Li et al 2005; Xie 2012; Cui et al 2001; Zhang et al 2008; Gao 2007).…”
Section: Introductionmentioning
confidence: 99%